A Study on Tourist Places in Nagapattinam District-Tamilnadu (Journal of Basic and Applied Research in Biomedicine, 2022)
Tourism is travel for recreational, leisure, or business purposes, usually of a limited duration. Tourism is commonly associated with trans-national travel, but may also refer to travel to another location within the same country. The World Tourism Organization defines tourists as people "traveling to and staying in places outside their usual environment for not more than one consecutive year for leisure, business and other purposes". Tamilnadu rich with scenic beauty is located at the southern part of india. Resourceful with all kind of verities including temples, wild life sanctuaries, waterfalls, cosmopolitan cities, valleys, hill resorts, beaches etc..., tamilnadu is a must visit state in india for all tourist enthusiasts and will not get disappointed. From chennai to kanniyakumari, tamilnadu has the most beautiful and amazing coastal landscape (Especially, marina beach, nagapattinam (kodikkarai), thanuskodi and kanniyakumari). This research Paper focus on the tourist places in nagapattinam district.